2021
DOI: 10.3390/biology10040327
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Dependence of Flight Performance in Ageing Drosophila melanogaster

Abstract: Similar to humans, insects lose their physical and physiological capacities with age, which makes them a convenient study system for human ageing. Although insects have an efficient oxygen-transport system, we know little about how their flight capacity changes with age and environmental oxygen conditions. We measured two types of locomotor performance in ageing Drosophila melanogaster flies: the frequency of wing beats and the capacity to climb vertical surfaces. Flight performance was measured under normoxia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 101 publications
4
8
0
Order By: Relevance
“…Our comparison of younger and older flies (10 vs. 25 days after eclosion) adds to this discussion, as we found no measurable differences in the maximal wing-beat frequency between our two age groups, indicating that this aspect of flight performance does not deteriorate drastically with insect age. In support of this hypothesis, Privalova et al [ 22 ] studied ageing patterns in more detail in the locomotion of D. melanogaster , reporting no systematic deterioration in the maximal wing-beat frequency with ageing, although the flies were monitored much longer than in our study, until the age of 50 days post eclosion. At the same time, Privalova et al [ 22 ] reported that their studied flies showed a systematic decrease in climbing capacity, another type of locomotory performance, which indicated that physiologically old flies were still able to flap their wings at frequencies comparable to their much younger conspecifics.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Our comparison of younger and older flies (10 vs. 25 days after eclosion) adds to this discussion, as we found no measurable differences in the maximal wing-beat frequency between our two age groups, indicating that this aspect of flight performance does not deteriorate drastically with insect age. In support of this hypothesis, Privalova et al [ 22 ] studied ageing patterns in more detail in the locomotion of D. melanogaster , reporting no systematic deterioration in the maximal wing-beat frequency with ageing, although the flies were monitored much longer than in our study, until the age of 50 days post eclosion. At the same time, Privalova et al [ 22 ] reported that their studied flies showed a systematic decrease in climbing capacity, another type of locomotory performance, which indicated that physiologically old flies were still able to flap their wings at frequencies comparable to their much younger conspecifics.…”
Section: Discussionsupporting
confidence: 86%
“…The flies exposed to our hypoxic condition (10% O 2 ) generally showed a lower maximal wing-beat frequency than the flies exposed to normoxia (21% O 2 ). Similarly, earlier studies have reported that fruit flies [ 22 , 112 ], honeybees [ 113 ], dragonflies [ 114 , 115 ] and locusts [ 116 ] exhibited decreased flight performance during acute exposures to conditions with lower oxygen availability.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations